Ni(II) Cylinders Damage DNA in Cancer Cells and Preferentially Bind Y-Shaped DNA Three-Way Junctions Blocking DNA Synthesis - Malina, Jaroslav; Kostrhunova, Hana; Brabec, Viktor (Small (Weinheim an der Bergstrasse, Germany), 2024)
DNA three-way junctions are critical in various biological processes and hold significant potential for disease treatment and therapeutic applications. In this study, it is demonstrated that triple-stranded dinuclear [Ni2L3]4+ cylinders (L = C25H20N4) exhibit a preferential binding affinity for Y-shaped DNA three-way junctions (3WJs), even in the presence of an excess of competing DNA structures, including G-quadruplexes. Notably, the investigated Ni(II) cylinders are capable of halting DNA synthesis catalyzed by DNA polymerase by stabilizing the 3WJ on the template strand. Using an extended 1D nanoarchitecture model, it is further established the high affinity and selectivity of the cylinders for DNA 3WJs and explored their potential application in stabilizing short-armed 3WJs for constructing DNA nanomaterials. The combined use of Ni(II) cylinders and DNA damage response inhibitors also revealed that the cylinders promote DNA damage, leading to the formation of double-strand breaks. This effect is likely associated with i) the binding of cylinders to 3WJs and ii) the cytotoxic activity of the cylinders in cancer cells.
Keywords: Humans; DNA three‐way junctions; DNA nanomaterials; DNA damage; lidé; DNA; nikl; DNA Replication; replikace DNA; G-Quadruplexes; Neoplasms; Nickel; nádorové buněčné linie; nádory; poškození DNA; DNA Damage; G-kvadruplexy; Ni(II) cylinders; cytotoxicity; Cell Line, Tumor